Pengaruh Giro Wadiah, Tabungan Wadiah, Dan Deposito Terhadap Pertumbuhan Laba Bersih Di PT. Bank Muamalat Indonesia - Maratul Munawaroh; Sucipto; Bambang Kurniawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
PT. Bank Muamalat Indonesia is one of the Islamic banking which has an important role almost the same as other banks and is tasked with collecting funds and distributing them to the public in the form of financing. Changes in profit can be influenced by deposit funds (wadiah current accounts and wadiah savings), and time deposits, assuming that wadiah demand deposits, wadiah savings, and time deposits. This study aims to determine how much influence Wadiah Current Account, Wadiah Savings, and Time Deposits on Net Profit Growth at PT. Bank Muamalat Indonesia. The type of research used in this research is quantitative research with a descriptive approach. The results showed partially that there was an effect of wadiah demand deposits on net income growth with a significance value of 0.001, there was an effect of wadiah savings on net income growth with a significance value of 0.050, and there was an effect of deposits on net income growth with a significance value of 0.018. Then simultaneously shows that there is an effect of wadiah demand deposits, wadiah savings and time deposits on the growth of net income at PT. Bank Muamalat Indonesia of 45.2% with a significance value of 0.005.